2020
DOI: 10.1038/s41598-020-63802-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Long-term Glycosylated Hemoglobin in Patients with Acute Myocardial Infarction: a retrospective cohort study

Abstract: Little clinical evidence supports the strict implementation of glycemic control for diabetic patients with AMI. We aimed to demonstrate the effect of long-term glycemic control on mortality in patients with diabetes mellitus after acute myocardial infarction (AMi). eight hundred and twenty-four consecutive diabetic patients were divided into three groups according to the mean hemoglobin (HbA1c) value: <6% (group A), ≥6% to <7.5% (group B), and ≥7.5% (group C). The best long-term mortality outcome was observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…Samefors et al [58], in a cohort of 698 patients with type 2 DM, found that low 25(OH)D3 is associated with an increased cardiovascular morbidity/mortality. In our population, diabetic patients had worse long-term outcomes when compared to non-diabetic patients, coherently with previously published data [59].…”
Section: Discussionsupporting
confidence: 92%
“…Samefors et al [58], in a cohort of 698 patients with type 2 DM, found that low 25(OH)D3 is associated with an increased cardiovascular morbidity/mortality. In our population, diabetic patients had worse long-term outcomes when compared to non-diabetic patients, coherently with previously published data [59].…”
Section: Discussionsupporting
confidence: 92%
“…Other studies often used admission HbA 1C values while we evaluated all values (not necessarily upon admission). The association between low and high HbA 1C and ∆HbA 1C with long-term mortality following AMI is consistent with a recent study by Lee et al [ 22 ] that evaluated the association of long-term mean HbA 1C with long-term survival following AMI. They reported that patients with a mean HbA 1C value ≥ 6.0% to <7.5% had a better prognosis than patients with HbA 1C values of <6.0% or >7.5%.…”
Section: Discussionsupporting
confidence: 90%
“…Lower glycemic levels can be attributed not only to intensive glycemic control. Other factors such as old age and comorbidities may cause low HbA 1C [ 22 , 27 , 28 , 29 , 30 ]. In addition, increased oxidative stress and endothelial dysfunction, which are markers of worse outcomes, were reported to be associated with significant glycemic changes [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations